Low risk of treatment resistance in Down syndrome with Kawasaki disease. Issue 12 (20th December 2017) - Takatsuki, Shinichi; Ogata, Shohei; Ishii, Masahiro; Yokozawa, Masato; Ono, Masae; Fujiwara, Masako; Ida, Hiroyuki; Motomura, Hideki; Moriuchi, Hiroyuki; Taketazu, Mio; Kawamura, Yoichi; Kawano, Tatsuya; et al.
Abstract: Background: A Japanese nationwide survey has reported that Down syndrome (DS) is a less‐frequently occurring comorbidity in Kawasaki disease (KD). Although altered immune responses are frequently observed in DS, no studies have focused on the treatment response and risk for coronary artery abnormalities (CAA) in DS patients with KD. The aim of this study was therefore to evaluate the clinical manifestations, treatment response and prevalence of CAA in DS with KD. Methods: We retrospectively reviewed the medical records of DS patients with KD from 2005 through 2012. The survey questionnaires were sent to facilities nationwide, and clinical data regarding KD in DS were collected. A control group consisted of non‐DS patients with KD who were managed at Toho University. Results: Of the 94 233 children diagnosed with acute KD from 2005 to 2012, 16 children with acute KD also had DS (0.017%). The DS‐KD patients were significantly older than the non‐DS patients (median, 8 years vs 1 year, P  <   0.05, respectively). Half of the DS patients had incomplete KD. Although 50% of the DS children were at high risk of immunoglobulin resistance, all children responded to initial treatment and none had CAA. Conclusions: All DS‐KD patients responded to initial i.v. immunoglobulin (IVIG) or aspirin despite having a high risk of IVIG resistance, and none of the DS patients had CAA. This suggests that the risk of treatment resistance and development of CAA may be not higher in DS patients with acute KD.